RNA Binding Proteins in Intestinal Epithelial Biology and Colorectal Cancer. Issue 5 (May 2018) - Chatterji, Priya; Rustgi, Anil K.
Abstract : The intestinal epithelium is highly proliferative and consists of crypt invaginations that house stem cells and villus projections with differentiated cells. There exists a dynamic equilibrium between proliferation, migration, differentiation, and senescence that is regulated by several factors. Among these are RNA binding proteins (RBPs) that bind their targets in a both context dependent and independent manner. RBP–RNA complexes act as rheostats by regulating expression of RNAs both co- and post-transcriptionally. This is important, especially in response to intestinal injury, to fuel regeneration. The manner in which these RBPs function in the intestine and their interactions with other pivotal pathways in colorectal cancer may provide a framework for new insights and potential therapeutic applications. Highlights: Intestinal epithelial cells harbor proliferation–differentiation gradient spanning crypts to villi. This is regulated by two stem cell populations. RNA binding proteins (RBPs) provide a nexus of regulation of intestinal epithelial homeostasis, adaptation to injury, and contribution to malignant transformation. These specific RBPs that have been reported in the published literature in the context of intestinal epithelial biology and colorectal cancer include: LIN28, Musashi (MSI), insulin-like growth factor 2 mRNA binding proteins (IGF2BP/IMP), MEX3A, CUGBP Elav-Like Family Member 1 (CELF1), RNA binding protein 3 (RBM3), and Hu-Antigen R (HUR). These specific RBPs play important roles in intestinal regeneration following injury. These specific RBPs are overexpressed in human colorectal cancer and overexpression of some of them has been shown to be sufficient to transform the intestinal epithelium in mouse models.